2019
DOI: 10.1038/s41419-019-1696-9
|View full text |Cite|
|
Sign up to set email alerts
|

FGF1ΔHBS ameliorates chronic kidney disease via PI3K/AKT mediated suppression of oxidative stress and inflammation

Abstract: Currently, there is a lack of effective therapeutic approaches to the treatment of chronic kidney disease (CKD) with irreversible deterioration of renal function. This study aimed to investigate the ability of mutant FGF1 (FGF1 ΔHBS , which has reduced mitogenic activity) to alleviate CKD and to study its associated mechanisms. We found that FGF1 ΔHBS exhibited much weaker mitogenic activity than wild-type FGF1 (FGF1 WT ) in renal tissues. RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…486,487 Recently, Huang et al 488 engineered the FGF1 mutants (termed FGF1 ΔHBS ) with reduced ability to activate FGFR, and found that FGF1 ΔHBS inhibited inflammation and oxidative stress in CKD via activating PI3K/AKT and GSK-3β/Nrf2 signaling pathways, which inhibited the ASK1/JNK. 489 The results suggest that FGF1 bears the responsibility of anti-inflammation, especially in certain chronic inflammatory diseases. Besides, FGF1 has the ability of anti-inflammation in diabetic nephropathy via inhibition of JNK (c-Jun N-terminal kinase) and NF-κB pathways.…”
Section: Fgf Signaling In Inflammatory Responsementioning
confidence: 96%
“…486,487 Recently, Huang et al 488 engineered the FGF1 mutants (termed FGF1 ΔHBS ) with reduced ability to activate FGFR, and found that FGF1 ΔHBS inhibited inflammation and oxidative stress in CKD via activating PI3K/AKT and GSK-3β/Nrf2 signaling pathways, which inhibited the ASK1/JNK. 489 The results suggest that FGF1 bears the responsibility of anti-inflammation, especially in certain chronic inflammatory diseases. Besides, FGF1 has the ability of anti-inflammation in diabetic nephropathy via inhibition of JNK (c-Jun N-terminal kinase) and NF-κB pathways.…”
Section: Fgf Signaling In Inflammatory Responsementioning
confidence: 96%
“…On the other hand, treatment with the peptide hormone Elabela activated PI3K/Akt/mTOR and reduced renal inflammation in diabetic mice by decreasing CCL2, ICAM-1, and TNF-α production [241]. In the same line, an engineered partial agonist of fibroblast growth factor-1 (FGF1 ∆HBS ) showed antioxidative effects and anti-inflammatory activities in db/db mice and also reduced oxidative stress and proinflammatory gene expression in podocytes challenged with high glucose by activating PI3K/Akt signaling [242]. Resveratrol has also shown to prevent experimental DN by regulating PI3K/Akt components in kidney tissue [243].…”
Section: Pi3k/akt/mtormentioning
confidence: 99%
“…Both inflammation and oxidative stress are reported to be closely associated with HG-induced podocyte injury in the development of DN. 18,19 The amplified and continued production of inflammatory cytokines including TNF-α, IL-1β and IL-6 can be induced by exposure of podocytes to HG. 20 Additionally, NLRP3 inflammasome is known to act as a sensor and is shown to be involved in inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%